Extraction of highly crystalline and thermally stable cellulose nanofiber from Heliconia psittacorum L.f. leaves - Paul, Sharon; Joseph, Anto; Hridhya, P. D.; Badawi, Michael; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Asrofi, Mochamad; Dominic, C. D. Midhun (International Journal of Biological Macromolecules, 2025)
Extracting cellulose nanofibers (CNF) from agro-waste is one of the promising and practical ways to develop sustainable nanocomposites. In this study, cellulose nanofibers were extracted from the leaves of Heliconia psittacorum for the first time. The combination of oxalic acid hydrolysis (5 wt%) and steam explosion was used for the isolation of CNF from the leaves of Heliconia psittacorum. The structural and chemical features of the prepared CNF were analyzed using various techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Solid state 13C Nuclear Magnetic Resonance Spectroscopy (13C NMR), Scanning Electron Microscopy (SEM), Energy Dispersive X ray analysis (EDX), Transmission electron Microscopy (TEM), X-Ray Diffraction (XRD) and Thermogravimetric analysis (TGA). TEM micrographs reported 15 to 40 nm diameter for the nanofibers synthesized. XRD analysis reported 91 % crystallinity index for CNF, whereas that of the untreated sample was 76 %. The maximum degradation of the CNF is reported at 355 degrees C, exceeds the untreated sample (316 degrees C). The tensile strength of the CNF derived paper was found to be 23 MPa. The recovered nanocellulose can be further utilized for various applications such as the automobile industry for developing lightweight parts, biosensors, super capacitors, absorption of greenhouse gases, wastewater treatment, and packaging applications.
Keywords: biomass valorization; Nanocellulose; Waste to resource

Sustainable isolation of cellulose nanofibers with superior crystallinity and thermal stability from Terminalia catappa L. fruit peel waste - Harsha, R.; Mol, A. P. Princy; Paul, Sharon; Badawi, Michael; Ajithkumar, T. G.; Rao, H. Jeevan; Parameswaranpillai, Jyotishkumar; Nair, Ajalesh B.; Begum, P. M. Sabura; Dominic, C. D. Midhun (Biomass Conversion and Biorefinery, 2025)
Turning agricultural waste into value-added products is a key focus of sustainable development. Herein, cellulose nanofibers (CNF) were extracted from the pericarp of Terminalia catappa L. for the first time. The CNF was extracted by chlorine-free pretreatment methods followed by oxalic acid hydrolysis (5 wt%) assisted with steam explosion. The prepared CNF were characterized by Fourier transform infrared spectroscopy (FTIR), solid-state 13C nuclear magnetic resonance spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA and DTG). FTIR analysis confirmed the successful removal of lignin and hemicellulose during chemical treatment which was again validated by solid-state 13C NMR analysis. TEM image revealed that the diameter of the extracted nanofibers ranges from 14 to 18 nm. From XRD analysis, the crystallinity index of the CNF was 82%, while that of the raw sample was 62 %. The temperature at which the maximum degradation (Tmax) of CNF occurred was found to be 372 degrees C which is superior to that of the raw sample (334 degrees C). The extracted cellulose nanofibers were used to prepare cellulose paper, demonstrating a tensile strength of 1.1 MPa, indicating its potential suitability for biodegradable packaging applications.
Keywords: cellulose; Cellulose nanofiber; green synthesis; Waste to wealth

Sustainable nanocellulose extraction from salacca zalacca peel using chlorine-free and low-acid treatments - Krishnan, Akhil; Paul, Sharon; Phiri, Resego; Srisuk, Rapeeporn; Kumar Singh, Manoj; Palaniappan, Sathish Kumar; Rangappa, Sanjay Mavinkere; Dominic, C. D. Midhun; Ajithkumar, Thalasseril G.; Siengchin, Suchart (ACS Omega, 2026)
Conversion of agro-waste to value-added products is one of the important principles of a green circular economy. A novel sustainable technique has been reported by using chlorine-free extraction of cellulose nanofibers (CNFs) from the peels of Salacca zalacca, a common fruit found in Asia. The fruit peels were exposed to alkali treatment using 2% NaOH (60 degrees C, 2 h), chlorine-free bleaching using 15% hydrogen peroxide (60 degrees C, 2 h), and sulfuric acid hydrolysis (15% v/v) for the extraction of CNFs. Various analytical methods were employed to characterize the prepared CNFs. The Fourier transform infrared spectroscopy (FTIR) and 13C solid state nuclear magnetic resonance (NMR) spectra showed the complete elimination of lignin and hemicellulose in the prepared CNFs. The elemental composition and high purity of CNFs were further verified by energy-dispersive X-ray analysis (EDX). The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images proved the fibrous morphology of the prepared CNFs, and the diameters of the cellulose nanofibers were found to be 15-30 nm. The X-ray diffraction (XRD) studies disclosed the type-I cellulosic structure in the prepared CNFs with a high crystallinity index (73%). The thermogravimetric analysis (TGA) demonstrated the superior thermal stability of the prepared CNFs (T max is 350 degrees C) compared to the raw fiber (T max is 320 degrees C). Based on the obtained results, it has been explored that the extracted highly pure CNFs can be used for fabricating bionanocomposites for high performance applications, including food packaging, sensors, water treatment, green tires, etc.